The Impact of the Great War on Urban Health: A Case Study of Contagious Diseases in the Dubrovnik Civil Hospital, 1914–1924 - Car, Antun (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2026)
Infectious diseases were a leading cause of mortality among soldiers and civilians during World War I. While most of these pathogens were known prior to the conflict, wartime conditions catalyzed their transition into widespread epidemics. Although vaccines for typhoid, cholera, and tetanus significantly reduced mortality, their implementation was often delayed or met with public resistance. This study analyzes the epidemiological profile of the Dubrovnik Hospital, which functioned as both a civil and military institution. Strict infection control was maintained, notably through mandatory smallpox vaccination for all hospital admissions. During the war, the hospital treated an average of 1,100–1,200 patients annually, one-third of whom were military personnel. While Dubrovnik recorded cases of louse-borne spotted typhus, it avoided the catastrophic outbreaks seen on the Eastern Front. However, the proximity of the Neretva River marshes, combined with the influx of infected soldiers, resulted in high malaria mortality. The final year of the war was marked by the emergence of the Spanish flu, which caused a high death toll in 1918 due to severe pulmonary complications. Tuberculosis remained a persistent threat throughout the period, while the high incidence of sexually transmitted diseases among soldiers significantly impacted military readiness. Other diseases such as diphtheria, tetanus, erysipelas, and scarlet fever further complicated the public health landscape. This research also addresses the challenges of fragmented archival records and the loss of documentation from the Military Garrison Hospital and St. James’s Lazaretto, which limits a complete statistical reconstruction of certain war years and child mortality rates.
Keywords: First World War; urban health; infectious diseases; Dubrovnik hospital; epidemiological profile; wartime medicine